Time Orientation and Decision Making Styles: The Case of Vietnamese Customers’ Purchase of Audiovisual Products - Dao, Tung (VNU Journal of Science: Policy and Management Studies, 2017)
This research aims to investigate the relationship between time orientation (past, future, and present orientation) and the decision making styles of Vietnamese customers when they decide to purchase a audiovisual product. A survey was conducted on 423 Vietnamese customers in Hanoi in 2016. The results demonstrate significant relationships between perspectives of time orientation and customer’s decision-making styles. Among the three time perspectives, the past and future orientation manifest a significant difference between decision making styles (customer segments). The present orientation was shown to have significant relationships with some individual characteristics of decision-making style, but no significant difference found between decision-making styles. Key words:     Time Orientation, Decision Making Styles (DMS), Vietnamese Customers, Audiovisual products.